RITUALS OF INITIATION AND TRANSITION AS A MEANS OF SOCIALIZATION OF AN INDIVIDUAL - Alexander V. Atamanov (Векторы благополучия: экономика и социум, 2023)
The relevance is caused by contemporary social issues such as breakdown of social structures, crisis in culture, search for identities, interethnic and interracial conflicts, formation of new social strata and hierarchies, reevaluation of moral and ethical norms, issues of gender inequality, challenging situations with migrants and refugees, emergence of religious sects, subcultures, extremist movements, and challenges of globalization. Adapting to the new structure of the social world, well-being of the individual in society, their understanding of their place in the world, and their awareness of belonging to a particular group require the search for guidance and a basis for successful socialization. The phenomenon of human life known as ritual plays this role. Through the dramatic enactment of these rituals, individuals internalize behavioral patterns, and the symbolic content of the ritual form contributes to the formation of the axiological significance of objects and phenomena present in human life. Serving as a symbolic representation of society structure, its hierarchical relationships and connections, rituals permeate the entire social structure and consistently accompany individuals, aiming to facilitate their socialization. The goal is to study initiation and transition rituals as means of individual socialization. Research methods include structural-functional and analytical approaches, philosophical analysis of texts, and analogy. The result of our study of initiation and transition rituals confirms their importance for individual socialization. For both the individual and the group as a whole, the entire ritual complex is essential as a means of self-actualizing worldviews, norms, values, and attitudes, as evidenced by the internal relation between rituals accepted in a particular social community.